Hamster polyomavirus-associated T-cell lymphomas in Syrian hamsters (Mesocricetus auratus). Issue 2 (March 2023) - Ito, Soma; Chambers, James K.; Son, Nguyen Vu; Kita, Chiaki; Ise, Ken-ichiro; Miwa, Yasutsugu; Nakayama, Hiroyuki; Uchida, Kazuyuki
Hamster polyomavirus (HaPyV) infection has been associated with lymphomas in Syrian hamsters. In the present study, 14 cases of lymphoma in pet Syrian hamsters were pathologically examined and the involvement of HaPyV was investigated. Among 14 cases, 11 were abdominal and 3 were cutaneous lymphomas. The average ages of hamsters with abdominal lymphoma and cutaneous lymphoma were 7 months (range: 4-12 months) and 14 months (range: 6-23 months), respectively. Histologically, abdominal lymphomas were characterized by the diffuse growth of tumor cells with intermediate or large nuclei, low mitotic rates, the presence of tingible body macrophages, and the T-cell immunophenotype. Furthermore, 4/11 abdominal lymphomas were immunopositive for T-cell intracellular antigen-1, suggesting cytotoxic T-cell lymphomas. Cutaneous lymphomas were diagnosed as nonepitheliotropic T-cell lymphoma. Polymerase chain reaction (PCR) detected HaPyV DNA in 12/14 samples, and a sequence analysis of PCR amplicons confirmed >99% nucleotide identity to the published HaPyV sequences. In situ hybridization (ISH) for HaPyV DNA resulted in diffuse nuclear signals within tumor cells in 10/14 cases. Consistent with previous findings, all HaPyV-associated lymphomas were observed in the abdominal cavity of young hamsters. Polymerase chain reaction and ISH were useful for identifying the involvement of HaPyV in lymphomas, and ISH results indicated the presence of episomal HaPyV in neoplastic lymphocytes. The present study suggests that HaPyV infection is highly involved in abdominal lymphomas in young pet Syrian hamsters in Japan and provides diagnostic information on HaPyV-associated lymphoma.